The Role of Virtual Classrooms on Developing Reflective Thinking in Islamic Education Among Students from Teachers’ Perceptions in UAE - Alyasein, Yahia; Chehdimae, Hamdan; Yussuf, Ahmad (Journal of Islamic Educational Research, 2025)
The research aimed to identify the role of virtual classrooms on developing reflective thinking in Islamic education among students from teachers’ perceptions in UAE. To achieve that, a quantitative design (descriptive-analytical approach) was used, and a questionnaire consisting of 30 items, distributed equally into two domains: the importance of employing virtual classrooms and the role of virtual classrooms in developing reflective thinking in Islamic education, was applied to a random sample of 467 Islamic education teachers. The results showed that the degree of importance of employing virtual classrooms in teaching Islamic education was (high), and the level of the role of virtual classrooms in developing reflective thinking in Islamic education among students was (high). The results also showed no significant difference in the degree of importance of employing virtual classrooms in teaching Islamic education due to (gender, educational stage, academic qualification, and years of experience) variables. Moreover, the results showed a significant difference in the role of virtual classrooms in developing reflective thinking in Islamic education among students due to the academic qualifications variable in favor of PhD and MSc, and experience variable in favor of less than 10 years’ experience, while no differences appeared due to (gender and educational stage) variables. According to these finding, the researchers recommend the necessity of continuing to employ virtual classrooms in teaching, even in normal circumstances, because of their prominent role in developing reflective thinking.